Pengaruh Kinerja Keuangan Terhadap Harga Saham Dengan Mediasi Nilai Perusahaan Pada Perusahaan Barang Konsumsi Primer Yang Terdaftar Di Bursa Efek Indonesia (Subsektor Food And Baverage 2018-2021) - Aisyah, Siti; Djuanda, Gustian (ARBITRASE: Journal of Economics and Accounting, 2022)
This study aims to determine how the effect of financial performance on stock prices and its impact on firm value in primary consumer goods companies listed on the Indonesian stock exchange (food and beverage sub-sector 2018-2021). The data collection method is the documentary data collection trace historical data on audited annual financial reports on the www.idx.co.id website. The type of research used is quantitative data analysis. The population and samples taken based on certain criteria or purposive sampling obtained a sample of 25 companies. The data is processed with SmartPLS version 3.3.9. The analysis includes path model, measurement (outer) model test, structural (inner) model test, model suitability test and model interpretation. The results showed that profitability and liquidity ratios had an effect on firm value, leverage ratios had no effect on firm value, profitability and liquidity ratios had a positive effect on stock prices, leverage had no effect on stock prices, firm value had no effect on stock prices, firm value could mediate the ratio of profitability and liquidity to stock prices but firm value cannot mediate leverage to share prices.